Tranexamic Acid and Blood Loss During and After Cesarean Section: A Prospective Randomized Study - Shabir, Noshina (International Journal of Pathology, 2019)
Objective: To find out the effectiveness and safety of tranexamic acid in the reduction of blood loss during and after the cesarean section. Methodology: A prospective, randomized, placebo controlled, study was directed on 100 women experiencing lower segment cesarean segment (LSCS) at Department of Obstetrics and Gynecology, Combined Military Hospital Muzaffarabad over 6 months from May 2018 to October 2018. Fifty of them were given tranexamic acid preceding LSCS were contrasted and 50 control group who got IV placebo. Blood loss was collected and estimated during two periods. The study group got IV tranexamic acid and the control group got IV placebo. Following delivery, all participants got 10 units of oxytocin in 500 mL of normal saline. Hemoglobin, urine examination, liver and renal functions were checked in both the groups. Results: Tranexamic acid essentially decreased the quantity of blood loss from the finish of LSCS to 2 hours postpartum: 60.96±13.4 ml in the investigation group versus 112.02±13.46 mL in the control group (p=0.001). It additionally essentially reduced the amount of blood loss– Intraoperative 500.62±111.20 mL in the study group, versus 696.85±196.32 ml in the control group. (P<0.001). No serious complication or reactions were accounted for in either group. Conclusion: Tranexamic acid essentially decreased the quantity of blood loss during and after the lower segment cesarean segment and its utilization was not associated with any serious reactions or side effect like thrombosis. TXA can be utilized as safe and effective in participants undergoing LSCS and useful for anemic women or the individuals who refuse blood transfusion